2015
DOI: 10.1136/annrheumdis-2015-208268
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase-activated receptor 2 modulates OA-related pain, cartilage and bone pathology

Abstract: ObjectiveProteinase-activated receptor 2 (PAR2) deficiency protects against cartilage degradation in experimental osteoarthritis (OA). The wider impact of this pathway upon OA-associated pathologies such as osteophyte formation and pain is unknown. Herein, we investigated early temporal bone and cartilage changes in experimental OA in order to further elucidate the role of PAR2 in OA pathogenesis.MethodsOA was induced in wild-type (WT) and PAR2-deficient (PAR2−/−) mice by destabilisation of the medial meniscus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 24 publications
(27 reference statements)
8
70
0
Order By: Relevance
“…Indeed, we previously showed that the BV/TV decreased early after DMM, at week 4 but not at weeks 6 and 9 23. To the difference of Stattic, MR16-1 significantly decreased the extent of synovitis, which occurred early in the DMM model 29 34. This suggests that MR-16 might act through other pathways than Stat3 in the synovium tissue.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, we previously showed that the BV/TV decreased early after DMM, at week 4 but not at weeks 6 and 9 23. To the difference of Stattic, MR16-1 significantly decreased the extent of synovitis, which occurred early in the DMM model 29 34. This suggests that MR-16 might act through other pathways than Stat3 in the synovium tissue.…”
Section: Discussionmentioning
confidence: 92%
“…The use of the micro-CT technique to assess therapeutic interventions is already being applied in other disease states (Bougioukli et al, 2015; Rusckowski et al, 2016). Similarly, micro-CT imaging is already being relied on in pre-clinical transgenic models involving genetic alterations and transcriptional modifications (Huesa et al, 2015; Keller et al, 2013). This novel technology provides high sensitivity in lesion detection with a spatial resolution of 19-μm isotropic voxel size.…”
Section: Applications and Discussionmentioning
confidence: 99%
“…PAR2‐deficient mice also showed protection from cartilage damage in the DMM model of OA (Ferrell et al ., ; Amiable et al ., ; Jackson et al ., ), which has limited inflammation. Further studies on murine DMM indicated that PAR2 deficiency delayed osteophyte maturation (Huesa et al ., ), which reflects the previously observed delay in callus formation during bone fracture repair (Georgy et al ., ; O'Neill et al ., ). This suggests a role for PAR2 in driving pathogenic chondrocyte differentiation and/or maturation, separate from its pro‐inflammatory action.…”
Section: Proteinase‐activated Receptorsmentioning
confidence: 97%